Exploration of Ethnomathematics on the Traditional Musical Instrument Serunai in Bengkulu - Wahyu Setyo Utomo; Kashardi Kashardi; Selvi Riwayati (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study aims to explore the ethnomathematical concept embedded in the traditional musical instrument Serunai Bengkulu, with a focus on its geometric and symmetrical elements. Serunai, a local cultural heritage, has a physical form that reflects mathematical concepts, such as a cylinder, a truncated cone, and a circle. Using a descriptive qualitative approach with ethnographic methods, data were collected through direct observation, interviews with cultural experts, and visual documentation. The results show that parts of the Serunai, such as the funnel, stem, and ornaments, exhibit vertical and rotational symmetry, as well as geometric shapes consistent with mathematics learning materials at the Junior High School (SMP) level. Integrating local cultural elements into mathematics learning can provide a contextual learning experience, increase student interest, and bring mathematics closer to everyday life. These findings support the importance of implementing ethnomathematics in education, particularly in efforts to preserve local culture and to strengthen understanding of mathematical concepts in more meaningful ways. This study also recommends using cultural objects, such as musical instruments. traditional in learning as a contextual medium to introduce the concepts of geometry and symmetry to students.